Clinical pharmacist-initiated assessment and amelioration of appropriate antibiotic use in surgical units at a South Indian tertiary care hospital - A handshake approach - Ann Vazhayil Kuruvilla; Ramesh Madhan; Madhu Chandagal Puttaswamy (Journal of Infection in Developing Countries)
Introduction: Studies on the appropriateness of antibiotic use among surgical patients are limited in developing countries, notably in India. Therefore, we aimed to evaluate the inappropriateness of antibiotic use, demonstrate the impact of clinical pharmacist interventions and determine the predictors of inappropriate use of antibiotics in the surgical units of a South Indian tertiary care hospital.